Current state of poultry waste management practices in Bangladesh, environmental concerns, and future recommendations (Journal of Advanced Veterinary and Animal Research, 2022)
This review paper focuses on the current state of poultry waste generation, composition, and management techniques in commercial poultry farms and trading in Bangladesh, to reduce pollution and generate economic benefits from poultry waste. It also underlines the negative impact of poultry waste disposal on the environment. In Bangladesh, collection of poultry waste into bags and, subsequently, direct use as fertilizer in agricultural fields and aquaculture is common, while alternative disposal methods such as composting and biogas generation are now attracting commercial poultry producers. Direct use of poultry manure results in poor air and soil quality, environmental deterioration, detrimental effects on global health, climate change due to high levels of atmospheric ammonia, and the creation of significant amounts of greenhouse gases. Lack of knowledge and investment, as well as high demand for free land for composting, are important obstacles. Future research on precise waste characterization, improved understanding of poultry waste management, and increased efforts on developed waste disposal for a safe environment are therefore recommended. So, poultry waste, which is currently a burden for the environment, could be turned into a useful agricultural resource, which would be useful for the poultry industry.    J. Adv. Vet. Anim. Res., 9(3): 490–500, September 2022http://doi.org/10.5455/javar.2022.i618